Foliar feeding of boron improves the productivity of cotton cultivars with enhanced boll retention percentage. (1st October 2020) - Wahid, Muhammad Ashfaq; Saleem, Muhammad; Irshad, Sohail; Khan, Shahbaz; Cheema, Mumtaz Akhtar; Saleem, Muhammad Farrukh; Tung, Shahbaz Atta
Abstract: Cotton ( Gossypium hirsutum L.) is of prime importance because of its quality fiber and edible oil production. Boron (B) is among essential micronutrients for plant growth; it aids in the transfer of sugars and nutrients from leaves to fruit that are involved directly or indirectly in many plant functions. Cotton growth, yield and quality are strongly affected with boron application. A two-year study was conducted to evaluate the impact of foliar applied B (0, 2, 4, 6, 8 and 10 g of B L −1 of water) on the performance of cotton cultivars (FH-113, MNH-786 and CIM-496). The results indicated that growth, yield and quality traits of cotton were significantly influenced by different levels of foliar applied boron as well as cultivars of cotton. Among cotton cultivars, the yield and quality parameters were superior in cultivar "FH-113." Foliar application of boron at 6 g L −1 of water improved leaf area index and leaf area duration and eventually improved the number of bolls per plant, boll retention percentage, average boll weight, lint yield, ginning out turn, fiber length and uniformity ratio of cotton. Foliar application of B at 6 g per liter of water, showed promising results by improving growth and quality parameters and is recommend to enhance the economical yield production of cotton cultivar "FH-113" with improved quality.